Pakistan Brain Tumour Epidemiology Study (PBTES): Uncovering the Hidden Burden of Brain Tumours in the Country - Syed Ather Enam; Sameen Siddiqi; Mohammad Hamza Bajwa; Mashal Murad Shah; Muhammad Usman Khalid (Journal of the Pakistan Medical Association, 2022)
Epidemiological studies have significantly helped determine the burden, types, and geographical distribution of brain tumours in HICs (highincome countries). However, brain tumour data from low-and-middle-income countries is often sparse, focusing on a few centres1. The situation in Pakistan is no different. Few oncological registries exist in our region that focus on common tumours. Collecting data regarding brain tumours has been challenging, as evidenced by the underreported incidence of brain tumours by centers such as the Karachi Cancer Registry (KCR), Pakistan Atomic Energy Commission (PAEC) report, and GLOBOCAN. Brain tumours are distinct from other cancer types by having more than 200 subtypes, requiring complex analysis, grading, and personalized therapeutic strategies. Moreover, there is no current standardized system to record brain tumour patient data, making it difficult to collate data from various centers. Continue.